Requerimientos de proteínas y lípidos en crías de Petenia splendida (Günther, 1862) (Perciformes: Cichlidae) - Matsumoto Soulé, José Jiro (Universidad Autónoma Metropolitana, 2010)
The approximate levels of dietary proteins and lipids that would sustain growth and feed efficiency in fingerlings of Bay Snook Petenia splendida (Günther, 1862) were determined in a feeding experiment. The experiment was carried out in a recirculating-water system (RWS) with twelve 40L-glass recipients within an initial density of 17 fish per recipient. Six fish-meal and soybean extrudes were formulated to contain three levels of protein (30, 40 and 50%) as well corn and fish oils were used to reach two levels of lipids (6 and 12%), with dietary gross energy ranging from 17.6 to 19.4 MJ kg⁻¹ and digestible energy fluctuating from 13.7 to 16.5 MJ kg⁻¹ . Fishes were fed with the diets for 120 days in duplicates groups in fingerlings of Bay Snook with an average initial weight of 0.18 ± 0.05 g. The results indicated significant differences among the experimental diets. Survival rates (76.5 to 97.1%); average final total weights (0.625 to 0.927 g); gain of average total weights (31.65 to 71.34%); specific growth rate (1.17 to 1.57 % day⁻¹ ); individual feed intakes (0.46 to 0.62 g) and protein efficiency ratio (2.87 to 6.10) were affected by different dietary treatments and condition factor (1.10 to 1.31) and food conversion ratio (0.87 to 1.8) did not present differences between experimental diets. Diet containing 50% of proteins and 12 % lipids had significant differences (P !0.05) and higher mean values of average final total weights, gain of average total weight, specific growth rate, individual feed intake, protein efficiency ratio, and survival rate. The results also indicated that the diet containing 50% of protein and 12% of lipids, 19.3 MJ kg⁻¹ of gross energy and 16.5 MJ kg⁻¹ of digestible energy was suitable for growth and feed efficiency in fingerlings of Bay Snook under the experimental conditions used in this study.; Se realizó un experimento utilizando seis dietas prácticas con diferentes niveles de proteínas y lípidos para determinar el desempeño del crecimiento y la eficiencia alimentaria de crías de Tenguayaca Petenia splendida (Günther, 1862). Se utilizó un sistema cerrado de recirculación (SCR) formado por 12 recipientes de vidrio con capacidad de 40 L y una densidad inicial de 17 organismos por recipiente. Las dietas se formularon con harina de pescado y extrudizado de soya para contener tres niveles de proteína (30, 40 y 50%) y aceites de maíz y de pescado para obtener dos niveles de lípidos (6 y 12%), con una energía bruta que varió de 17.6 a 19.4 MJ kg⁻¹ y una energía digerible que fluctuó de 13.7 a 16.5 MJ kg⁻¹ . Las dietas experimentales fueron suministradas durante 120 días por duplicado a crías con un peso total promedio inicial de 0.18 ± 0.05 g. Los resultados indicaron interacciones significativas entre las distintas dietas experimentales. La tasa de sobrevivencia (76.5 a 97.1%); peso promedio final (0.625 a 0.927 g), ganancia de peso total (31.65 a 71.34%), tasa específica de crecimiento (1.17 a 1.57 % día⁻¹ ), consumo individual de alimento (0.46 a 0.62 g), tasa de eficiencia proteica (2.87 a 6.10), factor de condición (1.10 a 1.31) y el factor de conversión de alimento (0.87 a 1.80) presentaron diferencias significativas (P !0.05) entre los tratamientos. La dieta con 50% de proteína y 12% de lípidos presentó diferencias significativas (P !0.05) y los valores más altos de peso promedio final, ganancia de peso total, tasa específica de crecimiento, consumo individual de alimento, tasa de eficiencia proteica y sobrevivencia. Los resultados indican que una dieta conteniendo 50% de proteína y 12% de lípidos con 19.3 Mj kg⁻¹ de energía bruta y 16.5 Mj kg⁻¹ de energía digerible es la más adecuada para el crecimiento y eficiencia del consumo de alimento de las crías de Tenguayaca bajo las condiciones experimentales utilizadas en este estudio.